Epistemologi Islam Dalam Tinjauan Filosofis - Umi Kulsum (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2020)
Branch epistemology is from the scientific discipline of knowledge that discusses its nature, scope, and limitations. This study is a means of solving a fundamental question. In Islamic thought, there are three epistemological structures, namely Bayani, Irfani, dan Burhani. Bayani epistemology, is defined as athought that emphasizes the authority of the texs (nas), which means understanding the texs as knowledge without any interpretation. While the epistemology of Irfani is called presented knowledge (hudluri Science). This epistemology is developed and used in sufi society. While epistemology Burhani, can be defined as an activity to realize the truth of a proposition (qadhiyah ) through a deductive approach developed by many philosophical figures.